Answer:
a = 10, b = 6, c = 2, d = 0
Step-by-step explanation:
Substitute the appropriate values of x into the equation and evaluate
x = - 3 : y = 4 - 2(- 3) = 4 + 6 = 10 → a
x = - 1 : y = 4 - 2(- 1) = 4 + 2 = 6 → b
x = 1 : y = 4 - 2(1) = 4 - 2 = 2 → c
x = 2 : y = 4 - 2(2) = 4 - 4 = 0 → d
Answer:
-1
Step-by-step explanation:
-49-35x+x=-3x-18
-49-34x=-3x-18
-34x+3x=-18+49
-31x=31
-31x/-31=31/-31
ansx=-1
pliz mark my answer brainliest
Answer:
Step-by-step explanation:
1) 8
2) ?
3) g=7
4) v=6
5)x=-4
6) p=8
now #2 i havent learnd yet but all the others. EASYYYYY i love math just choose me if you are having troubles in algebra at all i got you bro <3
Answer:
1 3/4
Step-by-step explanation:
you have to convert the mixed numbers into improper fractions first
2 1/2 turns into 5/2
then you make the denominators the same
5/2 turn into 10/4
then you subtract
10/4 - 3/4 = 7/4
then you turn it into a mixed number
7/4 turns into 1 3/4